Stem cell delivery of therapies for brain disorders - Alexander Aleynik (Clinical and Translational Medicine, 2014)
Abstract The blood brain barrier (BBB) poses a problem to deliver drugs for brain malignancies and neurodegenerative disorders. Stem cells such as neural stem cells (NSCs) and mesenchymal stem cells (MSCs) can be used to delivery drugs or RNA to the brain. This use of methods to bypass the hurdles of delivering drugs across the BBB is particularly important for diseases with poor prognosis such as glioblastoma multiforme (GBM). Stem cell treatment to deliver drugs to neural tumors is currently in clinical trial. This method, albeit in the early phase, could be an advantage because stem cells can cross the BBB into the brain. MSCs are particularly interesting because to date, the experimental and clinical evidence showed ‘no alarm signal’ with regards to safety. Additionally, MSCs do not form tumors as other more primitive stem cells such as embryonic stem cells. More importantly, MSCs showed pathotropism by migrating to sites of tissue insult. Due to the ability of MSCs to be transplanted across allogeneic barrier, drug‐engineered MSCs can be available as off‐the‐shelf cells for rapid transplantation. This review discusses the advantages and disadvantages of stem cells to deliver prodrugs, genes and RNA to treat neural disorders.